The Antagonistic and Synergistic Role of Fe3+ Compounds in Chemo- and Electrochemotherapy in Human Colon Cancer In Vitro - Wojciech Szlasa; Wiktoria Mazurek; Anna Szewczyk; Nina Rembiałkowska; Joanna Tunikowska; Julita Kulbacka (MDPI AG, 2024)
Colon cancer (CC) management includes surgery, radio- and chemotherapy based on treatment with 5-fluorouracil (5-FU) or its derivatives. However, its application is limited to low-grade carcinomas. Thus, much research has been conducted to introduce new techniques and drugs to the therapy. CC mostly affects older people suffering from cardiac diseases, where iron compounds are commonly used. Ferric citrate and iron (III)-EDTA complexes have proven to be effective in colon cancer in vitro. This study aimed to determine the potency and action of iron-containing compounds in colon cancer treatment by chemo- and electrochemotherapy in both nano- and microsecond protocols. The viability of the cells was assessed after standalone iron (III) citrate and iron (III)-EDTA incubation. Both compounds were also assessed with 5-FU to determine the combination index. Additionally, frataxin expression was taken as the quantitative response to the exposition of iron compounds. Each of the substances exhibited a cytotoxic effect on the LoVo cell line. Electroporation with standalone drugs revealed the potency of 5-FU and iron(III)-EDTA in CC treatment. The combination of 5-FU with iron(III)-EDTA acted synergistically, increasing the viability of the cells in the nanosecond electrochemotherapy protocol. Iron(III)-EDTA decreased the frataxin expression, thus inducing ferroptosis. Iron(III) citrate induced the progression of cancer; therefore, it should not be considered as a potential therapeutic option. The relatively low stability of iron(III) citrate leads to the delivery of citrate anions to cancer cells, which could increase the Krebs cycle rate and promote progression.